2022
DOI: 10.3390/ma15020497
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organizational Evolution on the Stress Corrosion Cracking of the Cr-Co-Ni-Mo Series of Ultra-High Strength Stainless Steel

Abstract: Different microstructures were obtained under various thermal conditions by adjusting the heat treatment parameters of the Cr-Co-Ni-Mo series of ultra-high strength stainless steel. The effect of organizational evolution on the stress corrosion cracking (SCC) of the Cr-Co-Ni-Mo series of ultra-high strength stainless steel was investigated using potentiodynamic polarization curves, electrochemical impedance spectroscopy (EIS), transmission electron microscopy (TEM), scanning electron microscopy (SEM) and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
(65 reference statements)
0
0
0
Order By: Relevance
“…Numerous studies have shown that the regulation of quenching temperature has a significant impact on organizational and mechanical properties [6][7][8][9][10]. Shi et al [11,12] analyzed the effects of water volume, jet angle, and jet pressure on the cooling rate during ultra-rapid cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that the regulation of quenching temperature has a significant impact on organizational and mechanical properties [6][7][8][9][10]. Shi et al [11,12] analyzed the effects of water volume, jet angle, and jet pressure on the cooling rate during ultra-rapid cooling.…”
Section: Introductionmentioning
confidence: 99%
“…The volume mismatch was caused by the difference of atomic size, which led to serious lattice distortion effect and hindered the dislocation movement to strengthen the materials [18][19][20]. For instance, the addition of elements such as C [21,22], Ti [23], Al [23][24][25], Mo [26,27], and others to CoCrNi or CoCrFeMnNi MPEAs can significantly improve the mechanical properties of the alloys. The addition of Al element to the CoCrNi alloy resulted in the formation of (CoCrNi) 87 Al 13 .…”
Section: Introductionmentioning
confidence: 99%